Comparison of Coffee Stain Removal Effects of Commercial Whitening Toothpaste in Sound and Demineralized Teeth In Vitro - Ji-Hyun Min (The Korean Society of Dental Hygiene Science, 2023)
Background: The size of the tooth whitening market and toothpaste market is increasing worldwide. The purpose of this in vitro study is to confirm and compare the coffee stain removal effects of commercial whitening toothpaste in sound and demineralized teeth, respectively.Methods: A total of 112 flat permanent bovine teeth specimens were manufactured. Half of the surface of the specimen was coated with an acid-resistant varnish and deposited in an artificial demineralizing solution for 65 hours. The varnish applied to half of the specimen was removed and deposited in a coffee solution for 96 hours to induce coloring. Two control and five experimental group toothpastes for teeth whitening were selected and the main components were investigated. Toothbrushing was performed 50, 100, and 150 times for each toothpaste group. A total of four images were obtained: before the start and after 50, 100, and 150 times of brushing to obtain the lightness (L*) values of the sound and the demineralized tooth surfaces. The difference in the average value between toothpaste groups at each treatment period was analyzed by one-way ANOVA. The difference in the L* average value according to the number of the brushing was analyzed by repeated measure ANOVA. Results: All toothpastes in the seven groups contained abrasive agents and had different ingredients for each product. Compared to before brushing, the L* value changed significantly in all toothpaste groups after brushing 50 times (p＜0.05). This was common in both the sound and demineralized teeth surfaces. Demineralized teeth had significantly lower L* values at all brushing times than that in sound teeth (p＜0.05). Conclusion: The effect of whitening teeth was different for each toothpaste. Demineralized teeth were more likely to cause coloration than sound teeth, and the coloration was not removed well.